A Comparison of Immediate and Post-Session Feedback with Behavioral Skills Training to Improve Interview Skills in College Students. Issue 3 (2nd October 2019) - Barker, Laura-Katherine; Moore, James W.; Olmi, D. Joe; Rowsey, Kyle
ABSTRACT: Successful interviewing skills help maximize the probability that a job candidate will make a positive impression upon a prospective employer. Previous research described a method to increase appropriate interview skills using Behavioral Skills Training (BST) with post-session feedback. Immediate feedback has been shown as an effective method that may improve the effectiveness and efficiency of the training package described by previous research. The purpose of this study was to replicate past studies using BST to improve interview skills of college students and extend the study by comparing post-session and immediate feedback. All participants demonstrated improvements in interview skills, thus replicating previous findings. More specifically, BST with immediate feedback showed greater acquisition, maintenance, and generalization, with fewer training minutes required to meet mastery criteria compared to BST with post-session feedback.